2013
DOI: 10.1371/journal.pone.0071021
|View full text |Cite
|
Sign up to set email alerts
|

Consideration Of Chronic Pain In Trials To Promote Physical Activity For Diabetes: A Systematic Review Of Randomized Controlled Trials

Abstract: BackgroundChronic pain has been estimated to affect 60% of patients with diabetes and is strongly associated with reduced activity tolerance. We systematically reviewed randomized controlled trials (RCTs) that explored interventions to improve physical activity among patients with diabetes to establish whether co-morbid chronic pain was captured at baseline or explored as an effect modifier and if trials reported a component designed to target chronic pain.Methodology/principal FindingsWe searched CINAHL, Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Few RCTs have specifically examined the effects of exercise training on chronic pain in people with type 2 diabetes. In a systematic review of 136 RCTs investigating interventions to improve physical activity levels in people with diabetes, only one reported chronic pain measures at baseline and no trials investigated chronic pain as a target of the intervention [30]. Since this review, the Italian Diabetes and Exercise study published data from their RCT of 606 inactive people with type 2 diabetes comparing twice weekly supervised aerobic and resistance training plus counselling versus counselling alone for 12 months [11].…”
Section: Discussionmentioning
confidence: 99%
“…Few RCTs have specifically examined the effects of exercise training on chronic pain in people with type 2 diabetes. In a systematic review of 136 RCTs investigating interventions to improve physical activity levels in people with diabetes, only one reported chronic pain measures at baseline and no trials investigated chronic pain as a target of the intervention [30]. Since this review, the Italian Diabetes and Exercise study published data from their RCT of 606 inactive people with type 2 diabetes comparing twice weekly supervised aerobic and resistance training plus counselling versus counselling alone for 12 months [11].…”
Section: Discussionmentioning
confidence: 99%
“…In the aforementioned Cochrane review, only 25% of the studies included actively reported adverse events [87]. Another systematic review of randomized controlled trials in people with T2D found only 1 of the 136 exercise trials evaluated pain at baseline, and no trials were designed to specifically target the chronic pain [110]. The Italian Diabetes and Exercise Study used tailored exercise programs to minimize the risk of injury and worsening of RMS so to improve exercise adherence [85].…”
Section: Evaluation Of Rheumatological and Musculoskeletal Symptoms And Chronic Painmentioning
confidence: 99%
“…Боль при ОА и СД2Т является общим и основным клиническим симптомом, ограничивающим трудоспособность. В частности, 60% больных СД2Т испытывают хроническую боль, связанную со снижением толерантности к глюкозе [162]. Кроме того, у больных СД2Т часто наблюдается боль в спине, верхних и нижних конечностях, абдоминальная и нейропатическая боль [163][164][165].…”
Section: молекулярные механизмы боли при остеоартрите и сахарном диабетеunclassified